Медична ботаніка – пріоритетний напрям наукових досліджень сьогодення - Dzhurenko, N.I.; Palamarchuk, O.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Data about foundation and development of the Laboratory of Medicinal Botany at M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are presented. The periods of medicinal plants collection formation and expansion, scientific branches and modern status of medicinal botany researches are elucidаted.